2022
DOI: 10.3390/ijerph19148841
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Self-Perceived Parenting Attitudes on Visuo-Spatial Attention and Mental Rotation Abilities among Adolescents

Abstract: The present study aimed to investigate the effect of adolescents’ perceived negative evaluation of parenting on their visuo-spatial attention and mental rotation abilities. The useful field of view (UFOV) and mental rotation tasks were used to measure visuo-spatial attention and mental rotation abilities among adolescents. The experimental groups were divided into the negatively evaluating group (MAge = 18.44, SD = 0.87, 20.7% girls) and positively evaluating group (MAge = 18.40, SD = 0.81, 23.3% girls) based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…As we explore the relationship between parental psychological control and mental imagery, we find a limited number of studies directly investigating how the former impacts the latter. In a recent study by Kim, Baik, and Nam [ 47 ], it was revealed that adolescents’ self-perceived parenting attitudes significantly influence their cognitive performance. This influence is notably reflected in a decline in visuo-spatial attention ability and the adoption of an impatient strategy for mental imagery.…”
Section: Introductionmentioning
confidence: 99%
“…As we explore the relationship between parental psychological control and mental imagery, we find a limited number of studies directly investigating how the former impacts the latter. In a recent study by Kim, Baik, and Nam [ 47 ], it was revealed that adolescents’ self-perceived parenting attitudes significantly influence their cognitive performance. This influence is notably reflected in a decline in visuo-spatial attention ability and the adoption of an impatient strategy for mental imagery.…”
Section: Introductionmentioning
confidence: 99%